Primary School Students' Learning Anxiety during the COVID-19 Pandemic - Anggraeni, Sri Wulan; Alpian, Yayan; Kodariah, Siti (Universitas Pendidikan Ganesha, 2021)
This study aims to determine how elementary school students' learning anxiety during the COVID-19 period. This research method uses a qualitative descriptive approach with observation data collection techniques, interviews, and questionnaires. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The subjects in this study were elementary school students, teachers, and the participation of students' parents. The results of this study indicate that the level of learning anxiety of elementary school students during the COVID-19 pandemic did not show a high level of anxiety or was still limited and still considered light, did not cause excessive anxiety. Besides, the role of parents in accompanying and guiding students to study at home is quite effective in overcoming student learning anxiety. Various efforts were made to overcome student learning anxiety during the COVID-1 pandemic. These findings concluded that the anxiety experienced by elementary school students was still within normal limits.